A review on Quaternary tectonic and nontectonic faults in the central sector of the Iberian Chain, NE Spain - Gutiérrez, F.; Gracia, F.J.; Gutiérrez, M.; Lucha, P.; Guerrero, J.; Carbonel, D.; Galve, J.P. (Journal of Iberian Geology, 2012)
Several grabens superimposed on the previous contractional structures have been developed in the central sector of the Iberian Chain during the post-orogenic stage. Teruel and Calatayud grabens were formed in a first rifting phase (Miocene-Lower Pliocene). The second extensional phase is recorded by Late Pliocene-Quaternary grabens superimposed and/or inset with respect to the previous basins (Río Grío, Munébrega, Daroca and Jiloca depressions). This article reviews the existing knowledge on the main Quaternary faults (distribution, seismogenic potential) in the study area and discusses its limitations: (1) Two new grabens (Río Grío and Munébrega) have been recently documented on the basis of geomorphological mapping, suggesting that our knowledge on the distribution of Quaternary faults in the Iberian Chain is still limited. (2) Available data on cumulative displacement and long-term slip rate is scarce for a number of faults mainly due to the lack of correlatable markers on both sides of the faults and/or lack of numerical dates. (3) Our capability to estimate earthquake recurrence and elapsed time is largely limited due to the scarcity of paleoseismological data. Only the Munébrega W Fault and the Concud-Teruel Fault have been studied. The paleoearthquake record inferred for the former is probably under-represented and the latter fault has received different interpretations. The paper also includes the main results of a trenching investigation carried out in a graben generated by interstratal dissolution of evaporites, which allowed us to propose some criteria that may help to differentiate between tectonic (seismogenic) and gravitational (nonseismogenic) faults.